LEAF APPEARANCE RATE AND PHYLLOCHRON ON MILLET SOWING DATES - Somavilla, Felipe Manfio; ​Cargnelutti Filho, Alberto; Neu, Ismael Mario Márcio; Silveira, Daniela Lixinski; Bubans, Valéria Escaio; Dumke, Gabriel Elias (REVISTA BRASILEIRA DE MILHO E SORGO, 2023)
The objective of this study was to determine the leaf appearance rate and phyllochron as affected by millet sowing dates. The experiment was conducted with six sowing dates (11/28/2019, 12/03/2019, 12/10/2019, 12/17/2019, 12/30/2019 and 01/14/2020). The sowing was performed in plots with six rows of 2 m length and spacing of 0.25 m between rows. After emergence, for each sowing date, five plants were marked and the number of leaves was counted twice a week until flowering. For each plant relative to each sowing date (30 plants), the number of leaves (NL), leaf appearance period (LAP, in days), accumulated thermal sum (TSa, in ºC day), leaf appearance rate (LAR, on days leaf-1) and phyllochron in °C day leaf-1 were determined. Among the sowing dates, there is no variation in the number of leaves, with an average of 18.07 leaves. LAP varies between 49 and 88 days, TSa between 697.57 and 1299.47 °C day, LAR between 3.26 and 5.40 days leaf-1, and phyllochron between 45.05 and 80.81 °C day leaf-1. Millet shows better vegetative development (lower LAP, TSa, LAR and phyllochron) in early sowing (11/28/2019, 12/03/2019 and 12/10/2019) compared to later sowing (12/17/2019, 12/30/2019 and 01/14/2020).